Social co-governance and enlightenment of the EU food safety risk communication system - CHEN Zhenxing (Shipin yu jixie)
In the EU food safety risk communication system, social work system architecture can be summarized for the organization management system to build unified coordination of social work foundation, risk communication mechanism level to promote the bridge of information sharing and collaboration, the system advantage for the way of diversified communication to meet the demand of diverse information, a wide range of participants to ensure comprehensive and effective diversification mechanism. Efficient information sharing can improve response speed, scientific evaluation and independent regulation to ensure objectivity and scientific nature. China's food safety risk communication system in social work displays a diversity of communication methods; however, it has not yet established effective comprehensive information channels to promote collaborative efforts. The wide range of participants has not been able to consolidate their influence into a cohesive workforce. To strengthen public participation and build trust, it is essential to continue improving these systems and deepen the engagement in social work. To this, in the EU food safety risk communication system based on social work advantages, from relying on the optimization organization management system to build a unified and coordinated social work framework, with the help of innovation widely participate in the risk of communication mechanism to promote information sharing and collaboration, by improving public participation to deepen the social work pattern of different dimensions, to China's food safety risk communication system of social work to review and optimization.